STABILISASI TANAH LEMPUNG EKSPANSIF DENGAN MENGGUNAKAN CAMPURAN ABU-SEKAM DAN KAPUR - Herry Widhiarto; Aris Heri Andriawan; Andik Matulessy (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Soil as the foundation of a building must have a carrying capacity that is capable of supporting the load of the building on it. For this type of soil of clay that has a large shrinkage and development properties (expansive clays) as a result of which contained mineral montmorillonite minerals form very easily affected by changes in water content so easily expands further damaging buildings on it. To reduce the fluffy nature of clay is necessary to repair / stabilization by adding mix-husk ash and lime. In this study, carried out by the addition of a mix-husk ash and lime with variations in the percentage of 0%, 4%, 6% and 8%. The results show the value of plasticity index, IP, decreased by 59.35% on a mix-husk ash and lime at 6%, the greater the percentage of mix-husk ash and lime, dry density value,Â  increasing dry unit weight, decreasing swelling occurs quite 4% greater in percentage mix-husk ash and lime, the CBR value increased with the increasing percentage-husk ash and lime.Keywords: expansive clay, montmorillonite minerals, plasticity index, swelling, dry density, CBR.